Analyzing the expansion of timbric possibilities in the Concert Piece for timpani and orchestra by Mauricio Kagel - Matheus Augusto Ribeiro; Antenor Ferreira Correa (Per Musi, 2023)
The goal of this article is to pinpoint some effects that expand timbric possibilities for the use of timpani. For this purpose, the work Konzertstück fur Pauken und Orchester, by Mauricio Kagel, will be used as an example. This concert has been commented, above all, taking into account its scenic aspects, since Kagel acquired notoriety in the style known as musical theater. However, alongside these aspects determined for performance, the Concert Piece for Timpani and Orchestra presents innovative procedures related to timbric exploration on the timpani. These procedures, in addition to expanding the repertoire of possibilities specified in manuals and orchestration treatises, also present challenges to the instrument's performance technique. In this sense, this article considers the innovations created by the composer and proposes to expand the scope of procedures prescribed in the literature on writing for timpani.